A novel high-durability proton exchange membrane and its preparation method and application

By combining the liquid phase radical quenching method with the perfluorosulfonic acid resin dispersion system, a new high-durability proton exchange membrane was prepared, which solved the problem of the existing membrane's performance degradation in high temperature and low humidity environments, and achieved the high durability and excellent antioxidant and water retention properties of the membrane.

CN119542480BActive Publication Date: 2025-04-08JIANGSU YUANHYDROGEN NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510096377.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-08
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

The existing proton exchange membranes are prone to lose moisture in high temperature and low humidity environments, resulting in reduced performance, and free radical quenchers are prone to agglomeration and settlement in the membrane, affecting the durability of the membrane.

Method used

The liquid phase radical quenching method is highly adapted to the perfluorosulfonic acid resin dispersion system. Through the cooperation of modified silicon and manganese dioxide, a new high-durability proton exchange membrane is prepared to ensure the antioxidant performance and water retention ability of the membrane.

Benefits of technology

It significantly improves the durability of the proton exchange membrane, reduces the settlement and agglomeration of the modified materials, and ensures that the fuel cell maintains a higher conductivity and less voltage attenuation rate in high temperature and low humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542480B_ABST
    Figure CN119542480B_ABST
Patent Text Reader

Abstract

The invention discloses a novel high-durability proton exchange membrane and its preparation method and application, wherein a liquid-phase free radical quencher containing sulfonated silica and manganese ions is prepared using silicon dioxide, 3-mercaptopropyltriethoxysilane, hydrogen peroxide and manganese dioxide as raw materials; a casting liquid is prepared by mixing and preparing a perfluorosulfonic acid resin, a water / n-propanol solvent and a liquid-phase free radical quencher; the casting liquid is coated on a substrate and dried to obtain a proton exchange membrane. In the above manner, the preparation method of the present invention can significantly reduce the sedimentation and agglomeration of the modified material in the membrane, can have excellent water retention capacity in an environment with high temperature or water scarcity, and the performance of the membrane will not be impaired due to water shortage; the fuel cell using the present invention can maintain a high conductivity under high temperature and low humidity environments, and maintain a low battery voltage decay rate after long-term operation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cell materials, and in particular to a novel high-durability proton exchange membrane and a preparation method and application thereof. Background Art

[0002] Fuel cells use oxygen and hydrogen as reaction raw materials. When the operating voltage decays during operation, some of the oxygen is not completely oxidized on the electrode surface, producing active oxides, such as free radicals HOO• and HO•. These free radicals are in an unstable state and are highly active. They can react with some carbon atoms on the tetrafluoroethylene skeleton to cause carbon atoms to fall off, thereby destroying the tetrafluoroethylene skeleton and affecting the life of the proton exchange membrane.

[0003] Kinetic studies have shown that the movement speed of substances will increase significantly at high temperatures, so proton exchange membrane fuel cells need to operate in high temperature environments. At high temperatures, water evaporates, the ambient humidity decreases, the proton exchange membrane loses water, and the performance is greatly reduced, which in turn affects the performance of the fuel cell. Therefore, it is very necessary to improve the durability of the proton membrane.

[0004] Patent CN111244513A discloses a method for preparing a high-temperature fuel cell proton exchange membrane with the addition of a free radical quencher - cerium dioxide or manganese dioxide. The addition of a free radical quencher improves the antioxidant capacity of the proton membrane and improves the water retention capacity at high temperatures. Patent CN107221692A also discloses a polybenzimidazole / phosphoric acid multilayer composite high-temperature proton exchange membrane with high antioxidant capacity and a preparation method thereof. The free radical quencher used is silicon oxide-loaded manganese oxide or silicon oxide-loaded cerium oxide, which can be used in a high temperature environment of 120~200℃.

[0005] Manganese dioxide or cerium dioxide has good free radical quenching ability, and silicon dioxide has strong moisture absorption performance. These substances have significant effects on improving the water retention capacity of the membrane and enhancing the antioxidant property. However, the above patents all add the free radical quencher directly into the membrane dispersion in the form of a solid, which has the problem of agglomeration and dispersion. Summary of the invention

[0006] The main technical problem solved by the present invention is to provide a new type of highly durable proton exchange membrane and its preparation method and application, which can utilize the free radical quenching method in the liquid phase and is highly compatible with the perfluorosulfonic acid resin dispersion system, effectively improving the durability of the membrane, while not being easy to agglomerate and settle, thereby ensuring the performance of the fuel cell.

[0007] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide a method for preparing a novel high-durability proton exchange membrane, comprising the following preparation steps:

[0008] (1) Preparation of modified silicon: sulfonated silica is prepared by conventional methods. A certain amount of raw silicon dioxide is weighed and reacted with 3-mercaptopropyltriethoxysilane MPTMS using water as solvent to graft sulfur-SH modification on the surface of silicon dioxide. After the reaction is completed, the product is washed with water, filtered and dried to finally obtain modified silicon. As an inorganic substance, silicon dioxide has a certain hygroscopicity. Sulfonation of silicon dioxide can further improve its hydrophilicity and increase its water retention capacity.

[0009] (2) Preparation of liquid-phase free radical quencher: All the modified silicon prepared in step (1) is reacted with sufficient hydrogen peroxide to oxidize the sulfur group -SH to a sulfonic acid group, and then a small amount of manganese dioxide MnO2 is added to decompose the hydrogen peroxide; in the presence of sufficient hydrogen peroxide and an acidic environment, the manganese dioxide is inactivated and converted into an ionic form and dissolved in hydrogen peroxide, and the remaining hydrogen peroxide is transferred for microwave radiation decomposition; a small amount of MnO2 is added to a sample to observe whether gas is generated and determine whether it is completely removed. Then, the volume is concentrated under vacuum at room temperature, and the concentrated volume is controlled to obtain a liquid-phase free radical quencher with the required silicon content;

[0010] (3) Preparation of proton membrane casting solution: commercially available perfluorosulfonic acid resin, water / n-propanol solvent and the liquid phase free radical quencher prepared in step (2) are mixed in a certain proportion, first dispersed by ultrasonication and then heated and stirred to prepare a casting solution;

[0011] (4) Preparation of proton exchange membrane: The casting solution in step (3) is coated on a substrate, heated and cured, and then dried to obtain a proton exchange membrane.

[0012] In a preferred embodiment of the present invention, in step (1), the raw material is hydrophilic silica with a particle size range of 5-20 nm, the mass ratio of silica, MPTMS and water is 1:1-5:20-60, the reaction time is 5-12 h, the reaction temperature is 70°C-90°C, the drying temperature of the reaction product is ≥60°C, and the drying time is ≥12 h to ensure sufficient drying.

[0013] In a preferred embodiment of the present invention, in step (2), the mass ratio of hydrogen peroxide to raw silicon dioxide is 20-50:1, the reaction time is 12-24 hours, and the hydrogen peroxide is 30% hydrogen peroxide.

[0014] In a preferred embodiment of the present invention, in step (2), the mass ratio of manganese dioxide MnO2 to raw silicon dioxide is 0.3-0.6:1, and MnO2 is added slowly in small amounts.

[0015] In a preferred embodiment of the present invention, in step (2), microwave radiation is carried out at room temperature, 20-40°C, and the time is sufficient to remove all hydrogen peroxide; the vacuum concentration temperature is less than 40°C, and the silicon content in the liquid phase free radical quencher is in the range of 2%-8%.

[0016] In a preferred embodiment of the present invention, in step (3), in the casting solution, the fixed mass ratio of water / n-propanol solvent is 1:3, the mass ratio of the liquid phase free radical quencher and water / n-propanol solvent is 1:20-50, and the mass fraction range of perfluorosulfonic acid resin in the casting solution is 10-30%.

[0017] In a preferred embodiment of the present invention, in step (4), the casting liquid is applied by a conventional coating method: the PET backing is laid flat on a blade coating machine (model: TBJ-Xa-XB), the blade spacing is adjusted, the blade speed is set, the heating temperature is adjusted to 60°C, the casting liquid is evenly applied on the PET backing, the blade is started to form a film, and the film is removed and dried after it is dried.

[0018] In a preferred embodiment of the present invention, in step (4), the drying method includes first drying at 80°C for 1 hour, then drying at 100°C for 1 hour, and finally drying at 120°C for 1 hour to obtain the proton exchange membrane.

[0019] Another technical solution adopted by the present invention is a novel high-durability proton exchange membrane, which is prepared by any of the above-mentioned methods for preparing the novel high-durability proton exchange membrane.

[0020] In a preferred embodiment of the present invention, the proton exchange membrane is applied to the technical field of fuel cells.

[0021] The beneficial effects of the present invention are:

[0022] 1. The innovative liquid phase system of the present invention is highly compatible with the perfluorosulfonic acid dispersion system, which significantly reduces the sedimentation and agglomeration of the modified material in the membrane, thereby increasing the service life of the membrane.

[0023] 2. The liquid-phase free radical quencher prepared by the method of the present invention can effectively improve the antioxidant performance of the proton membrane and has excellent water retention capacity in a high temperature or water-scarce environment. The performance of the proton exchange membrane will not be damaged due to water shortage, and its structural integrity and functionality will always be maintained;

[0024] 3. The fuel cell using the present invention can maintain a high conductivity in a high temperature and low humidity environment, and maintain a low battery voltage decay rate after long-term operation; BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0026] Figure 1 is a SEM image of the proton exchange membrane of Example 1 of the present invention;

[0027] Figure 2 It is the infrared characterization image of Example 1, Comparative Example 1 and raw materials;

[0028] Figure 3 It is the contact angle test diagram of Example 1 and Comparative Example 1;

[0029] Figure 4 This is a durability test of Examples 1-3 and Comparative Example 1: open circuit voltage attenuation rate test graph. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0031] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0033] In the description of the present invention, it should be noted that the terms "front", "rear", etc. indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, or the orientation or positional relationship in which the invention product is usually placed when in use, which is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0034] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "disposed" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0035] In the present invention, unless otherwise clearly specified and limited, a first feature being above or below a second feature may include the first and second features being in direct contact, or may include the first and second features not being in direct contact but being in contact through another feature between them. Moreover, a first feature being above, above, and above a second feature includes the first feature being directly above and obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being below, below, and below a second feature includes the first feature being directly below and obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.

[0036] The embodiments of the present invention include:

[0037] Implementation Case 1:

[0038] S1. Take 5g of raw silicon dioxide into 200g of deionized water solution, add 10g of MPTMS, heat and stir at 80℃ for 8h. Then filter, wash with deionized water 3 times, collect the filter cake and dry it at 80℃ for 12h, collect the solid to obtain modified silicon.

[0039] S2. Add the modified silicon of S1 to 150g of 30% hydrogen peroxide and stir at room temperature for 18h. Weigh 2g of MnO2 (commercially available AR) solid and add it in a fume hood. Start very slowly, as gas will be generated immediately after addition. Continue adding until all the gas is gone. Then transfer to a microwave synthesizer and irradiate with microwaves at 30°C. It usually takes more than 20min. Take a sample and add a small amount of MnO2 to observe whether the hydrogen peroxide is completely removed. Purpose: To prepare a free radical quencher with a 5% Si element content, and the total mass reaches 50g by concentration and water replenishment.

[0040] S3, take 25g of commercially available perfluorosulfonic acid resin, add it to 120g of water / n-propanol mixed solution, add 4g of liquid phase free radical quencher prepared in S2, first ultrasonically disperse for 40min, then stir at 50℃ until stirred evenly, to obtain a casting solution, wherein the resin content is about 20%, and the silicon content accounts for about 0.8% of the resin.

[0041] S4. Prepare the proton exchange membrane by conventional casting method. First, lay the PET backing on the coating machine, adjust the scraper spacing, set the scraper speed, and adjust the heating temperature to 60°C. Evenly apply the casting liquid on the PET backing, and start the scraper to make the film. When the membrane is dried, take it out and place it in a drying oven, first dry it at 80°C for 1h, then dry it at 100°C for 1h, and finally dry it at 120°C for 1h to prepare the proton exchange membrane.

[0042] Implementation Case 2:

[0043] S1. Take 5g of raw silicon dioxide into 300g of deionized water solution, add 25g of MPTMS, heat and stir at 80℃ for 8h. Then filter, wash with deionized water 3 times, collect the filter cake and dry it at 80℃ for 12h, collect the solid to obtain modified silicon.

[0044] S2, add the modified silicon of S1 to 250g of 30% hydrogen peroxide and stir at room temperature for 18h. Weigh 3g of MnO2 and slowly add it in a fume hood. Then transfer it to a microwave synthesizer and irradiate it with microwaves at 30℃ until a small amount of MnO2 is added to observe that the hydrogen peroxide has been completely removed. Purpose: To prepare a free radical quencher with 8% Si content, and the total mass reaches 30g by concentration and water replenishment.

[0045] S3, take 25g of commercially available perfluorosulfonic acid resin, add it to 82g of water / n-propanol mixed solution, add 3g of liquid phase free radical quencher prepared in S2, first ultrasonically disperse for 40min, then stir at 50℃ until stirred evenly, to obtain a casting solution, wherein the resin content is about 30%, and the silicon content accounts for about 1.0% of the resin.

[0046] S4. Prepare the proton exchange membrane by conventional casting method. First, lay the PET backing flat on the coating machine, adjust the scraper spacing, set the scraper speed, and adjust the heating temperature to 60°C. Apply the casting liquid on the PET backing, and start the scraper to make the membrane. When the membrane is dried, take it out and place it in a drying oven. First, dry it at 80°C for 1h, then at 100°C for 1h, and finally at 120°C for 1h to prepare the proton exchange membrane.

[0047] Implementation Case 3:

[0048] S1. Take 5g of raw silicon dioxide, add it to 100g of deionized water solution, add 5g of MPTMS, heat and stir at 80℃ for 8h. Then filter, wash with deionized water 3 times, collect the filter cake and dry it at 80℃ for 12h, collect the solid to obtain the modified silicon.

[0049] S2, add the modified silicon of S1 to 100g of 30% hydrogen peroxide and stir at room temperature for 18h. Weigh 1.5g of MnO2 and slowly add it in a fume hood until it is added. Then transfer it to a microwave synthesizer and irradiate it with microwaves at 30℃ for about 20min or more. Take a sample and add a small amount of MnO2 to observe whether the hydrogen peroxide is completely removed. Prepare a free radical quencher with a 2% Si element content, and make the total mass reach 117g by concentrating and replenishing water.

[0050] S3, take 25g of commercially available perfluorosulfonic acid resin, add it to 240g of water / n-propanol mixed solution, add 8g of liquid phase free radical quencher prepared in S2, first ultrasonically disperse for 40min, then stir at 50℃ until stirred evenly, to obtain a casting solution, wherein the resin content is about 10%, and the silicon content accounts for about 0.6% of the resin.

[0051] S4. Prepare the proton exchange membrane by conventional casting method. First, lay the PET backing on the coating machine, adjust the scraper spacing, set the scraper speed, and adjust the heating temperature to 60°C. Evenly apply the casting liquid on the PET backing, and start the scraper to make the film. When the membrane is dried, take it out and place it in a drying oven, first dry it at 80°C for 1h, then dry it at 100°C for 1h, and finally dry it at 120°C for 1h to prepare the proton exchange membrane.

[0052] Comparative Example 1:

[0053] The difference between Comparative Example 1 and Example 1 is that no modifier is added, that is, the perfluorosulfonic acid resin is dissolved in water / n-propanol solvent to make the resin mass fraction 20%. Then, the proton exchange membrane is prepared by direct coating method under the same conditions as Example 1.

[0054] The following is a comparative test of the proton exchange membranes prepared by the methods of Example 1 and Comparative Example 1 in terms of structure and performance:

[0055] 1) The proton exchange membrane of Example 1 was subjected to SEM testing. Figure 1 shown.

[0056] The proton exchange membrane of Example 1 was sampled for SEM testing. The reinforcing layer ePTFE and the sulfonic acid resin membrane (white part) constituted the main structure of the proton membrane SEM. The free radical quencher of modified materials silicon dioxide and manganese was distributed in the membrane layer structure in the form of nanoparticles A, and the modified particles were distributed relatively evenly.

[0057] 2) The proton exchange membranes of Example 1 (PEM Example 1) and Comparative Example 1 (PEM Comparative Example 1) were subjected to infrared testing, as shown in FIG. Figure 2 shown.

[0058] By observing the infrared test characterization curve, compared with Example 1 (PEM Example 1) and Comparative Example 1 (PEM Comparative Example 1), it can be found that the infrared characteristic peaks of the original membrane are all reflected in Example 1. And due to the addition of Si and Mn elements, the corresponding peak intensity changes. The main characteristic peak of SiO2 is around 1100cm-1 (Si-O-Si bond), and the characteristic peak of MnO2 is around 600cm-1 (Mn-O bond vibration), which is also reflected in the infrared of Example 1. Since Mn exists in the form of variable valence ions in the free radical quencher, the characteristic peak of Mn in the ionic form on the membrane of Example 1 is offset, and the content in the membrane is low, and the intensity is also reduced.

[0059] 3) The contact angle test of the proton exchange membrane of Example 1 and Comparative Example 1 was performed. Figure 3 shown.

[0060] Sulfonated SiO2 can improve the hydrophilicity of the membrane. Through the contact angle test, it can be found that the contact angle of the proton exchange membrane of Example 1 is less than 90°, the surface is hydrophilic, and the liquid can easily wet the solid; the contact angle of the proton exchange membrane of Comparative Example 1 is greater than 90°, which indicates that the surface is hydrophobic, and the liquid does not easily wet the solid. The hydrophilicity of the proton exchange membrane of Example 1 is significantly improved compared with that of Comparative Example 1.

[0061] 4) The electrochemical performance of the membranes of Examples 1-3 and the proton exchange membrane of Comparative Example 1 was tested.

[0062] As shown in Table 1, the conductivity test was conducted under low humidity of 23% and temperature of 80°C and 120°C, and the unit is S / cm.

[0063] Table 1:

[0064] Comprehensive performance results 80℃ 120℃ Example 1 0.091 0.082 Example 2 0.102 0.092 Example 3 0.096 0.086 Comparative Example 1 0.053 0.031

[0065] As can be seen from the table, the conductivity of the proton exchange membranes added with free radical quenchers in embodiments 1 to 3 under high temperature and low humidity environments is higher than that of comparative example 1, indicating that the addition of sulfonated silica in the membrane greatly improves the water retention performance.

[0066] The proton exchange membranes of Examples 1 to 3 and Comparative Example 1 were assembled into single cells, respectively. Figure 4 The voltage decay rate bar graph of a single cell running at an open circuit voltage for 500 hours shows that after 500 hours, the performance decay rate of the proton exchange membrane with free self-quenching (Examples 1-3) is significantly lower than that of Comparative Example 1, which indicates that the free radical quencher enhances the durability of the membrane.

[0067] In summary, the innovative liquid phase system of the present invention is highly compatible with the perfluorosulfonic acid dispersion system, which significantly reduces the sedimentation and agglomeration of the modified material in the membrane, thereby increasing the service life of the membrane. The liquid phase free radical quencher prepared by the method of the present invention can effectively improve the antioxidant properties of the proton membrane, and has excellent water retention capacity in high temperature or water-scarce environments. The performance of the proton exchange membrane will not be damaged due to lack of water, and its structural integrity and functionality are always maintained. The fuel cell using the present invention can maintain a high conductivity in a high temperature and low humidity environment, and maintain a low battery voltage decay rate after long-term operation.

[0068] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a novel high-durability proton exchange membrane, characterized in that: The method comprises the following preparation steps: (1) Preparation of modified silicon: weigh a quantitative amount of raw silicon dioxide, use water as solvent, react silicon dioxide with 3-mercaptopropyltriethoxysilane MPTMS, graft sulfur-SH modification on the surface of silicon dioxide, wash the product with water, filter and dry to obtain modified silicon; (2) Preparation of liquid-phase free radical quencher: all the modified silicon prepared in step (1) is reacted with a sufficient amount of hydrogen peroxide to oxidize the sulfur group -SH to a sulfonic acid group; a small amount of manganese dioxide MnO2 is then added to decompose the hydrogen peroxide, and the remaining hydrogen peroxide is transferred for microwave radiation decomposition until the hydrogen peroxide is completely removed; then the volume is concentrated under vacuum at room temperature, and the concentrated volume is controlled to obtain a liquid-phase free radical quencher with the required silicon content; (3) Preparation of proton membrane casting solution: mixing perfluorosulfonic acid resin, water / n-propanol solvent and the liquid phase free radical quencher prepared in step (2) in a certain proportion, first dispersing and then heating and stirring to prepare a casting solution; (4) Preparation of proton exchange membrane: The casting solution in step (3) is coated on a substrate, heated and cured, and then dried to obtain a proton exchange membrane.

2. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (1), the raw material is hydrophilic silica with a particle size range of 5-20 nm, the mass ratio of silica, MPTMS and water is 1:1-5:20-60, the reaction time is 5-12 hours, the reaction temperature is 70°C-90°C, the drying temperature of the reaction product is ≥60°C, and the drying time is ≥12 hours to ensure sufficient drying.

3. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (2), the mass ratio of hydrogen peroxide to raw silicon dioxide is 20-50:1, the reaction time is 12-24 hours, and the hydrogen peroxide is 30% hydrogen peroxide.

4. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (2), the mass ratio of manganese dioxide MnO2 to raw silicon dioxide is 0.3-0.6:1, and MnO2 is added slowly in small amounts.

5. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (2), microwave radiation is carried out at room temperature, 20-40°C, and the time is sufficient to remove all hydrogen peroxide; vacuum concentration at room temperature is less than 40°C, and the silicon content in the liquid phase free radical quencher is in the range of 2%-8%.

6. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (3), in the casting solution, the fixed mass ratio of water / n-propanol solvent is 1:3, the mass ratio of liquid phase free radical quencher and water / n-propanol solvent is 1:20~50, and the mass fraction range of perfluorosulfonic acid resin in the casting solution is 10~30%.

7. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (4), the casting liquid is applied by a conventional coating method: the PET backing is laid flat on the coating machine, the scraper spacing is adjusted, the scraper speed is set, the heating temperature is adjusted to 60°C, the casting liquid is evenly applied on the PET backing, the scraper is started to form a film, and when the film is dried, it is removed and dried.

8. The method for preparing a novel high-durability proton exchange membrane according to claim 1, characterized in that: In step (4), the drying method includes first drying at 80° C. for 1 hour, then drying at 100° C. for 1 hour, and finally drying at 120° C. for 1 hour to obtain a proton exchange membrane.

9. A novel high-durability proton exchange membrane, characterized in that: The novel high-durability proton exchange membrane is prepared by the preparation method of any one of claims 1 to 8.

10. The novel high-durability proton exchange membrane according to claim 9, characterized in that: The proton exchange membrane is applied to the technical field of fuel cells.

Citation Information

Patent Citations

  • Polybenzimidazole / phosphoric acid multi-layer composite high-temperature proton exchange membrane with high oxidization resistant capability and preparation method thereof

    CN107221692A

  • High-temperature fuel cell proton exchange membrane and preparation method and application thereof

    CN111244513A

  • Preparation process of composite membrane for fuel cell

    CN112599824A

  • Fuel cell composite proton exchange membrane and preparation method thereof

    CN112652795A